THE INFLUENCE OF ACTIVE KNOWLEDGE SHARING STRATEGIES ON LEARNING OUTCOMES - Mustafatin Janatun A.R.A; Rahma Dwi Andini (Universitas Negeri Makassar, 2018)
The purpose of this study was to influence of active knowledge sharing strategies on learning outcomes on limas and prisma. This type of research is experimental study with kuantitatif approach. Desain is a Posttest Only Control Group Design with active knowledge sharing strategies models on experimental class and conventional models on control class. Sampling with purposive sampling technique, while the determination of experimental class and control class at cluster random sampling, so that VIII-A is a experimental class and VIII-B is a control class. Data collection technique is direct observation techniques, test nultiple choice and dokumen akademik. Data were analyzed by t test where t (count) = 3,175 and t (table) = 2,025 means thitung > ttabel hypothesis H1 accepted. It can be concluded that there are significant use of Active Knowledge Sharing models for matematics student learning outcomes. Recommended to teachers can use Active Knowledge Sharing Model in the learning process